Sublingual Administration of Tacrolimus in Liver Transplant Patient with Intestinal Malabsorption - Aritz Merchán Flores; Mercedes Arenere Mendoza; Irene Navarro Pardo; María Ángeles Allende Bandrés (Indian Journal of Transplantation, 2025)
Immunosuppressive therapy after liver transplantation typically combines a calcineurin inhibitor, an antimetabolite, and corticosteroids. Tacrolimus, due to its narrow therapeutic margin and variability in blood levels, requires therapeutic drug monitoring (TDM). This case report describes a 37-year-old woman with a history of bariatric surgery who developed fulminant liver failure and underwent emergency liver transplantation in January 2024. Despite receiving oral prolonged-release tacrolimus (Advagraf®), TDM showed sustained subtherapeutic levels and elevated transaminases, leading to a type II acute rejection and re-transplantation. Given suspected tacrolimus malabsorption, a literature review suggested sublingual administration of immediate-release tacrolimus (Prograf®) as an alternative with an initial dosing ratio of 1:2 sublingual-to-oral. The patient was switched to 3 mg/12 h sublingual tacrolimus, with subsequent dose adjustments based on TDM. Therapeutic tacrolimus levels were achieved, and transaminases gradually normalized. Sublingual tacrolimus could be an effective strategy for achieving therapeutic levels in patients with intestinal malabsorption.